The Correlation Between Self-Efficacy and Academic Dishonesty Among Senior High School Students - Tsamara Audina Putri; Harahap, Dinda Permatasari (Universitas Negeri Medan, 2025)
This study aims to determine the relationship between self-efficacy and academic dishonesty among high school students. Self-efficacy refers to an individual’s belief in their ability to accomplish tasks and achieve specific goals. At the same time, academic dishonesty encompasses dishonest behaviors and violations of ethical standards in academic activities. This study employed a quantitative research method with a population of 346 students and a sample of 78 students selected using purposive sampling. The sample criteria in this study were students who had committed academic dishonesty as proven by screening results. Data were analyzed using Pearson’s product-moment correlation. The results indicated a correlation coefficient of -0.764 with a significance level of 0.000 (p < 0.05), demonstrating a significant negative relationship between self-efficacy and academic dishonesty. The coefficient of determination was 0.583, indicating that self-efficacy contributed 58.3% to the variance in academic dishonesty. Furthermore, a comparison between the hypothetical mean and the empirical mean revealed that students’ self-efficacy was relatively low, while the level of academic dishonesty was high. Therefore, the proposed hypothesis was accepted. Furthermore, based on the average score, the academic dishonesty score for male respondents was 50.76, while for female respondents it was 27.17. This indicates that the average academic dishonesty behavior was higher among male respondents than female respondents.